The effects of leader’s perceived empathy, group commitment and individualism on team cooperation, under “public goods game” - Núncio, Ana Teresa Seco (2021)
The concept of empathy, which corresponds to the capacity of an individual to understand and experience the feelings of other or, generally known as, the capacity to “put yourself in someone else’s shoes”, has been rising relevance, namely the importance and consequences of the capacity to demonstrate empathy, at the workplace. Our study aims to understand how perceived leader’s empathy influences team cooperation under monetary contingencies, and the role of participants’ cooperation, group commitment and individualism in this relation. For this purpose, we have conducted an experimental research with 83 students, using a “Public Goods Game” to test the cooperation among groups, while manipulating leader’s empathy under three different conditions (empathic leader, neutral and non-empathic leader). At the same time, we have measured individualism/competitiveness and organizational commitment using self-reports. Results show that (1) leader’s perceived empathy is positively correlated with cooperation and cognitive empathy appears as the only significant predictor of contribution; (2) group commitment is positively correlated with cooperation and normative commitment is the only significant predictor of contribution; and (3) individualism is negatively correlated with cooperation.